PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN PRODUK ADIDAS DI INDONESIA - Kuswoyo, Chandra; Kristianto, Aldo (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2025)
This study was conducted to examine the influence of brand image and product quality on customer loyalty toward Adidas Indonesia apparel products. The respondents involved in this research consisted of 110 individuals who had made more than one purchase of Adidas Indonesia products. Data were collected using an online questionnaire and analyzed using SPSS version 27.The results of the data analysis indicate that both brand image and product quality have a positive and significant effect on customer loyalty, both individually and jointly. The research model shows that these two variables explain 9% of the variation in customer loyalty. This suggests that many other factors beyond brand image and product quality also influence customer loyalty.The findings reinforce the importance for companies to develop strategies that enhance brand image through creatively packaged campaigns and collaborations with influencers. Additionally, maintaining product quality is essential to meeting customer expectations and sustaining long-term customer loyalty.